Effect of polyunsaturated phosphatidylcholine on immune mediated hepatocyte damage. Issue 8 (August 1983) - Neuberger, J; Hegarty, J E; Eddleston, A L; Williams, R
Abstract : Studies were carried out to investigate the mechanisms underlying the reduction of hepatocellular necrosis observed when polyunsaturated phosphatidylcholine was administered to patients with HBsAg negative chronic active hepatitis. After oral administration of the agent, the susceptibility of rabbit hepatocytes to both antibody dependent cell mediated cytotoxicity and mitogen induced lymphocyte cytotoxicity was substantially reduced. Short term in vitro incubation of either the hepatocytes or lymphocytes with polyunsaturated phosphatidylcholine had no effect on antibody dependent cell mediated cytotoxicity. As it has been shown that orally administered polyunsaturated phosphatidylcholine can be incorporated into the liver cell membrane, it is possible that polyunsaturated phosphatidylcholine exerts its effect by blocking the interaction between immune effector cells and hepatocytes.